TRENDS AND PROSPECTS OF AVIATION EQUIPMENT DEVELOPMENT - A. V. Levin; S. P. Khalyutin; B. V. Zhmurov (Научный вестник МГТУ ГА, 2016)
The article discusses the results of the aircraft electrical equipment development trends and prospects research based on the analysis of domestic and foreign manufacturers achievements. It is shown that the determining factor in the increasing electrification of aircraft equipment is energy efficiency and ecological compatibility. Theoretical and achieved quantitative characteristics of the units, devices, and elements of the electrical systems, which must determine the layout of advanced systems of electrical equipment are presented.